Relationship between Mathematics Performance and Anxiety - Fresan R. Magnate (International Journal on Integrated Education, 2022)
The purpose of this study was to explore the relationship between the indicator of mathematics anxiety and mathematics performance. The results indicated that the grade 12 students display a moderate level of anxiety in the subject. Moreover, small positive correlation between mathematics performance and when the students are worried that will not be able to use mathematics in their future careers when needed and if they will not be able to complete every assignment. Also, a small positive correlation between mathematics performance was noted when students feel stressed when listening to their instructor or teacher and when working on their homework. Lastly, a small positive correlation between mathematics performance was revealed when the student gets nervous when asking questions in mathematics class. From the context of this study, it was noted that we cannot simply say that automatically there is a negative correlation between MA and mathematics performance for it was revealed in this study that there are indicators of MA that correlates positively to the performance of students in a mathematics course. However, there were other indicators of MA that contribute negatively but were noted as having no relation to the mathematics performance.